PERFORMANCE EVALUATION OF FOOD BUSINESS INCUBATION CENTRE OF TAMIL NADU VETERINARY AND ANIMAL SCIENCES UNIVERSITY - N. Karpoora Sundara Pandian; I. Manikkavasagan; B. Guruprasath (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Food business incubation centre (FBIC) under the Tamil Nadu Veterinary and Animal Sciences University established during 2014 hadfacilitated the farmers, students and entrepreneurs in terms of training, consultancy, external project and incubation services. To evaluate the performance of the Food Business Incubation Centre on incubation services, data were collected for a period of 10 years from 2014-15 to 2023-24 and analyzed. The study also included the available data from the financial year 2018-19 to 2023-24 to assess the types ofvisitors and their purpose of visit to the incubation centre and the data were analyzed. It was concluded that majority of the incubatees utilized the FBIC for the incubation services in the area of dairy processing. Totally 14 members successfully graduated of which 50 % of them were female. The highest number of visits was recorded during the financial year 2022-2023 and the maximum of the visitor category was students from schools and colleges and only 9.7 % of the visitors were business aspirants out of the total visitors during the study period.